“Evaluación de bio estimulantes en el cultivo de tomate de árbol (Solanum Betaceum). en el cantón Mejía, provincia de Pichincha.” - Calapiña Noroña, Richard David (2022)
The tree tomato is an Andean fruit native to Bolivia used for jams, juices, ice cream, jellies, chili, among others. In Ecuador, tree tomato is grown mainly in the Sierra region. The province of Tungurahua is the most extensive due to the edaphic and environmental characteristics. The three main varieties grown are: common tomato, round tomato and blackberry tomato. It is estimated that 7,172 hectares are cultivated in Ecuador. Tree tomato crops in small and medium scales have yields between 20 and 30 mt/ha/year. Of the tree tomato production, 94.3% is destined for the local market for fresh consumption, 0.5% is used by agribusiness and 0.2% is for export. The research work was carried out in the Mejia Canton, Province of Pichincha, in order to test the evaluation of biostimulants in the cultivation of tree tomato (Solanum betaceum), based on the following objectives: To determine the agronomic behavior in the development of tree tomato, to establish phytosanitary control in the crop, to determine the agronomic effects with the application of biostimulants and to evaluate the yield per harvest treatment, for the realization of this project a Completely Winged Design (DCA) was proposed, presenting two biostimulants and a control. The variables under study were: plant height (cm), stem diameter (cm), number of leaves, number of flowers, number of fruits, the corresponding soil analysis was carried out for the improvement of the crop and soil in conjunction with the biostimulants. The results with the highest percentage were shown with treatment T1 (humic acids), represented with high values in plant height which were: 34.26, 84.76, 136.32, 184.51 and 184.71 cm at 21 days, 3, 9, 12, 14 months, likewise with higher percentage of stem diameter at 14 months with a value of 14.32 cm, respectively the number of leaves represented by 89.96%, the number of flowers with 76.80% at 12 months, number of fruits with 61.80%, proving that the Bio-stimulants based on humic acids who was the T1 treatment was the best acceptance for the development of tree tomato.